An Analysis Of Benefits In Sharia Perspective Of The Application Of Profit-Sharing Method On Mudharabah Savings - Nuur Rizka Putri Darmawanti; Virginia Nur Rahmanti (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
The study aims to explain the reasons for applying the savings scheme in the Mudharabah contract and the reasons for applying the profit-sharing method to the profit sharing of Mudharabah savings at KJPRI Brawijaya University. This research uses a qualitative method. The object of this research is the Savings and Loan Division of the Republic of Indonesia Employee Services Cooperative, Brawijaya University, Malang. This research uses a qualitative approach with a case study method. Data collection was conducted using a preliminary survey and source triangulation. The results showed that the reason KJPRI UB applied the Profit-Sharing method to Mudharabah savings was that Profit Sharing was considered more fair and humanitarian because the profits shared with members had been reduced by COGS and expenses or net profit, so that the existing expenses were charged to both parties, namely the owner of the capital (shahibul maal) and the business manager (mudharib).